North America $1 (BVolume 1s - Trollope, Anthony, 1815-1882 (Salt Lake City, UT : Project Gutenberg, 1999)
"North America $1 (BVolume 1" by Anthony Trollope is a travel narrative and cultural observation written during the mid-19th century, specifically in the period surrounding the American Civil War. The narrative results from Trollope's journey through the United States, wherein he examines various aspects of American life, including politics, society, education, and customs, amidst the climate of national discord. The text provides a lens through which readers can understand the complexities of American society at a pivotal moment in its history. At the start of the volume, Trollope sets the stage for his travels, detailing his motivations and expectations as he embarks on a journey through the United States from August 1861 to May 1862. He candidly discusses the Civil War's impact on his observations, emphasizing that while he aims to describe the American way of life, the ongoing conflict directs much of his commentary. He reflects on prior literary representations of Americans, indicating his desire to strike a balance between critique and admiration for the emerging nation and its people. As he begins his exploration, he notes the contrasting perceptions between Americans and Britons regarding the war, alongside the complex dynamics of their political relationships, thus establishing a rich premise for the travelogue that will unfold in the subsequent chapters. (This is an automatically generated summary.)s
Release date is 1999-08-01
E-text prepared by Donald Lainson and revised by Joseph E. Loewenstein, M.D.
Keywords: United States -- Description and travel; United States -- Politics and government -- 1861-1865; Canada -- Description and travel; Trollope, Anthony, 1815-1882 -- Travel -- North America